Strategi Politik dalam Pemenangan Pasangan Calon Bupati Malaka pada Pilkada 2024 : Studi pada Pemenangan Stefanus Bria Seran dan Hendri Melki Simu - Maria Relista B. Seran; Syahrin B. Kamahi; Frans W. Muskanan (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze the political strategies used by the candidate pair for Regent and Vice Regent of Malaka, Stefanus Bria Seran and Hendri Melki Simu (SBS-HMS), in winning the 2024 Regional Head Election (Pilkada) in Malaka Regency. This research is based on the local political phenomenon in which the SBS-HMS pair successfully gained broad public support through effective political communication and political marketing approaches. The research method employed is descriptive qualitative, with data collected through interviews, observation, and documentation. Data analysis is carried out using Firmansyah’s (2012) Political Marketing Theory, which includes three main aspects: political segmentation, political targeting, and political positioning. The findings reveal that the political strategy of the SBS-HMS pair was implemented systematically through voter segmentation based on socioeconomic backgrounds such as farmers, fishermen, youth, and women. The main campaign target focused on grassroots communities with strong loyalty. Meanwhile, the political positioning of the SBS-HMS pair was built through an image of experienced leadership, closeness to the people, and a strong commitment to regional development in Malaka. The conclusion of this study is that the success of the SBS-HMS pair in the 2024 Malaka Pilkada cannot be separated from well-planned political and communication strategies, grounded in community needs, and strengthened by an emotional connection between the candidates and voters.